2012
DOI: 10.12927/hcpol.2012.23016
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Management Literature for Insights into Implementing Evidence-Based Change in Healthcare

Abstract: Objective: We synthesized the management and health literatures for insights into implementing evidence-based change in healthcare drawn from industry-specific data. Because change principles based on evidence often fail to be translated into organizational practice or policy, we sought studies at the nexus of organizational change and knowledge translation. Methods: We reviewed five top management journals to identify an initial pool of 3,091 studies, which yielded a final sample of 100 studies. data were abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In addition, the journals other than Implementation Science, which published the highest number of citations in the broader D&I framework network, were all in the management and business fields. This is consistent with a prior review of leading management journals that found a significant degree of knowledge translation and organizational change literature relevant to D&I in healthcare [ 32 ]. While there is some current cross-over among these fields, they are often quite distinct and separate from each other when it comes to research and practice.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the journals other than Implementation Science, which published the highest number of citations in the broader D&I framework network, were all in the management and business fields. This is consistent with a prior review of leading management journals that found a significant degree of knowledge translation and organizational change literature relevant to D&I in healthcare [ 32 ]. While there is some current cross-over among these fields, they are often quite distinct and separate from each other when it comes to research and practice.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, when looking at the literature, authors of studies with primary relevance to implementation science typically publish almost exclusively in management literature [10]. This slows the spread of innovation because it stifles the extent to which research evidence for change purposes is sought, exchanged and applied [11,12]. Attention to change management principles in healthcare and educational settings is also important to avoid the use of inappropriate, ineffective strategies for implementation and hence save time and money [13].…”
Section: Change Management In Postgraduate Medical Educationmentioning
confidence: 99%
“…The scale of organisational change in health systems varies considerably from incremental (as in some internally generated work process improvements) through to rapid and large‐scale reforms driven by broader political, economic, or social factors . Despite extensive literature on organisational change management in general and in health systems in particular, there is little agreement on how system change is best managed and a lack of empirical evidence to guide decisions on what works, where, and why . This makes management of change difficult at best, and it remains the victim of a “strife of interests” between the different players in health systems including health professionals and patients as noted by Sax in 1984 .…”
Section: Change Management In Health Systemsmentioning
confidence: 99%
“…systems in particular, there is little agreement on how system change is best managed 20 and a lack of empirical evidence to guide decisions on what works, where, and why. 21 This makes management of change difficult at best, and it remains the victim of a "strife of interests" between the different players in health systems including health professionals and patients as noted by Sax in 1984. 22 Change management concerning comprehensive PHC is particularly difficult as it involves diverse players expressing varying values and ideas on comprehensiveness, empowerment, and engagement and holding different amounts of power.…”
Section: Introductionmentioning
confidence: 99%